Ethylene and gas exchange: A study on the impact on the in vitro development of Dipteryx alata seedlings - Marques, Elise Caroline Carvalho; Henrique Júnior, Afonso; Meira, Filipe Sathler; Dias, Leonardo Lucas Carnevalli (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2025)
Barueiro (Dipteryx alata Vog.) is a native species found in the Brazilian Cerrado, playing a significant role in the biodiversity of this biome, and holds significant economic value due to its versatile applications, including its seeds, which are widely used in the food and cosmetics industries. This study aimed to evaluate the effects of ethylene on the in vitro development of barueiro seedlings. Nine treatments were used to modify the in vitro environment: Control without gas exchange; Control with gas exchange; Ethylene without gas exchange; Ethylene with gas exchange; Potassium permanganate without gas exchange; Potassium permanganate with gas exchange; Control with atmosphere renewal on the 7th day; Ethylene added on the 7th day; and Potassium permanganate added on the 7th day. Phytotechnical parameters, such as shoot length, root length, stem diameter, shoot fresh weight, root fresh weight, shoot dry weight, and root dry weight, were evaluated. Among the parameters analyzed, only Leaf Area, Fresh Root Mass, Root Dry Mass, and Shoot Dry Mass showed statistically significant differences. The inhibition promoted by ethylene was not superior to having an environment with greater gas exchange restriction, and for some parameters, the simple fact of reduced gas exchange promoted effective inhibition. Therefore, it is recommended to use in vitro conditions that increase gas exchange, resulting in more vigorous barueiro seedlings with a greater capacity for morphogenic response. Index terms: Ambience; Cerrado; volatile.